Pengaruh e-wallet dan digital marketing terhadap kinerja keuangan UMKM - Aflagaly, Danar; Kusumowati, Dewi; Listyowati, Listyowati (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
This study aims to analyze the influence of e-wallets and digital marketing on the financial performance of MSMEs in Malang. This research utilizes primary data collected through questionnaires measured on a Likert scale. The respondents in this study are MSMEs that have adopted digital payment facilities and utilize digital marketing as a promotional medium for goods or services. The sample consists of 60 respondents selected using the purposive sampling method. The analysis method employed is multiple linear regression. The results indicate that e-wallets and digital marketing significantly impact the financial performance of MSMEs in Malang. This finding suggests that the adoption of digital technology in financial transactions and marketing contributes positively to the growth and sustainability of small and medium enterprises. Therefore, MSME owners are encouraged to optimize the use of e-wallets and digital marketing strategies to enhance their competitiveness, financial performance, and long-term business sustainability in Malang’s dynamic market environment.